Authoring war : the literary representation of war from the Iliad to Iraq - McLoughlin, Catherine Mary, 1970- (Cambridge : Cambridge University Press, 2011)
"Kate McLoughlin's Authoring War is an ambitious and pioneering study of war writing across all literary genres from earliest times to the present day. Examining a range of cultures, she brings wide reading and close rhetorical analysis to illuminate how writers have met the challenge of representing violence, chaos and loss. War gives rise to problems of epistemology, scale, space, time, language and logic. She emphasises the importance of form to an understanding of war literature and establishes connections across periods and cultures from Homer to the 'War on Terror'. Exciting new critical groupings arise in consequence, as Byron's Don Juan is read alongside Heller's Catch-22 and English Civil War poetry alongside Second World War letters. Innovative in its approach and inventive in its encyclopedic range, Authoring War will be indispensable to any discussion of war representation"--
Machine generated contents note: Introduction: authoring war; 1. Credentials; 2. Details; 3. Zones; 4. Duration; 5. Diversions; 6. Laughter; Conclusion: to perpetual peace; Bibliography; Index.
Includes bibliographical references and index.
Keywords: LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; War and literature